Pengaruh Struktur Modal, Likuiditas, Dan Intellectual Capital Terhadap Nilai Perusahaan - Ahmad Ramadhan; Julianto Agung Saputro (Universitas Galuh, 2026)
The development of the technology sector in Indonesia requires companies to be able to maintain their company value in the midst of increasingly fierce digital competition. This study aims to analyze the influence of capital structure, liquidity, and intellectual capital on the value of technology sector companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2024 period. The data used is secondary data in the form of annual financial statements obtained from the IDX's official website. This study uses a quantitative approach with a sample of 19 technology companies selected through the purposive sampling method. Data analysis was carried out using panel data regression with a Fixed Effect Model (FEM) approach. The results of the study show that capital structure does not have a significant effect on the value of the company, while liquidity and intellectual capital have a significant effect on the value of the company. These findings indicate that the company's ability to manage liquid assets and optimize intellectual capital is an important factor in increasing the value of technology sector companies in Indonesia.